First record of parasitoids of Phyllocnistis citrella Stainton (Lepidoptera: Gracillariidae) from Italy (Bollettino di zoologia agraria e bachicoltura, 2024)
The parasitoids Cirrospilus pictus (Nees) and Pnigalio agraules (Walker) (= mediterraneus Ferr. et Del.) (Hymenoptera Chalcidoidea Eulophidae) are recorded on Phyllocnistis citrella Stainton (Lepidoptera: Gracillariidae) in Italy.
Keywords: Phyllocnistis citrella; parassitoids; Italy